Pre-service art teachers’ perception of multicultural art education and teaching students from multicultural background: an exploratory study / Sherinaz Basree Abdul Rahman, Siti Zuraida Maaruf and Shireena Basree Abdul Rahman - Abdul Rahman, Sherinaz Basree; Maaruf, Siti Zuraida; Abdul Rahman, Shireena Basree (Penerbit UiTM (UiTM Press), 2018)
This study is an exploratory study designed to: (a) examine the current scenario and content of the Craft section in the Visual Art syllabus, (b) measure the preparedness of art teachers in teaching art among multicultural students and (c) identify the challenges that pre-service art teachers face in teaching multicultural art education. The Purposive Sampling method was employed where four (4) pre-service art teachers from the Art Education department from the Education Faculty of Universiti Teknologi MARA, Malaysia were chosen to be involved in the study. The data were collected via interview; hence, the research method for this study is predominantly qualitative in nature. Analyses of the data are explained based on the answers provided to the research questions.